Human posture recognition : an overview - Khalifa, Othman Omran; Htike, Kyaw Kyaw; Hassan Abdalla Hashim, Aisha; Lai, Weng Kin (IIUM Press, 2011)
Computer vision, which is a component of the field of artificial intelligence [1], is t~e study of methods and algorithms that enables machines and computers to "see" and "understand" images or multidimensional data [2]. In this context, the term, "understand", means that some information is being extracted from the image or video data for a particular purpose. The image or video data that is fed into a computer vision system is often a color or grayscale image [3] (obtained from a digital camera) but can also be stereo image (from a stereo camera) [4], video sequence (from a video camera) [5] or a 3D volume (from a tomography device). As a scientific discipline, computer vision aims to implement the theories of computer vision to the modeling of computer vision systems.